Adaptation of Resettled Rural Population towards Urban Life in Nanjing, China: from the Perspective of Resettled Residents - Liu, Pan (University of Waterloo, 2018)
The large-scale and continuing land acquisition in China is playing a positive role in regards to the national economic development while resulting in a number of issues among resettled rural residents. For the resettled residents who are forced to move into the city, it contains not only a geographical transformation but also a profound process of adaptation towards the economic, physical and social environment. Therefore, it is essential for the government to act on the issue to maintain social justice, stability as well as sustainability. The goal of this research is to study the adaptation conditions for resettled farmers, issues faced, and possible solutions. A model derived from Du and Pan (2014)’s study, along with other literature was developed to collect data from two selected communities in Nanjing, China. Data from three perspectives, economic adaptation, environmental adaptation, and social adaptation were gathered with a structured survey, and researching findings were derived from principal component analysis and descriptive analysis. Recommendations towards the planning process on resettlement were also proposed, such as encouraging public participation and taking farmers’ opinions into considerations. Policy recommendations based on the results of influencing factors and choices of potential improvements are derived from the perspectives of the farmers, including a high demand for information on social resources and investment, green space for vegetation plantations, and sufficient and diverse compensation and social insurance. The limitations of this study include the small sample size, the resettlement time differences between the two communities, and the subjectivism towards the questions. For future studies, a larger sample with a longitudinal survey can be proposed to derive participants from more communities, and a more reasonable evaluation measurement of the adaptation level can be designed to minimize the subjectivisms of the answers.
Keywords: urbanization; adaptation